Pendampingan Program P5 dalam Membentuk Karakter Berkelanjutan melalui Pelatihan Ekonomi Kreatif Daur Ulang di SMAN 2 Sangatta Utara - Pandiangan, Anjani Putri Belawati; Jumrianah, Jumrianah; Ali, Muhammad (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The integration of Pancasila values ​​in education faces various challenges, especially in the era of globalization, digitalization and social change. Today's students are exposed to a variety of external influences that can influence the understanding and application of these values. Globalization brings the influx of foreign cultures which often conflict with local values, including Pancasila. Implementation of the creative economy through recycled design can have a positive impact on local economic development. Student involvement in creative economic activities not only enriches their skills in the fields of design and production, but can also become social capital that supports community development. This research aims to find out how p support P5 in forming sustainable character through recycling creative economy training at SMAN 2 Sangatta Utara. The research method used in the research is a qualitative approach with a descriptive type. This research was conducted at SMA Negeri 2 Sangatta Utara. The informants in this research were Deputy Head of Curriculum, Subject Teacher, Students of North Sangatta 2 High School. Data collection was carried out using documentation, observation and interview techniques. Based on research results, it shows that this program provides space for students to gain a holistic learning experience, supporting character formation based on Pancasila values. Creativity and environmental awareness through recycled design shows students' ability to think creatively and innovatively. Through preparing teaching modules, monitoring activities, and evaluating programs, teachers ensure that P5 objectives are achieved effectively. With this approach, the environmental culture that has become part of the school's vision is increasingly embedded in students' lives, both through intracurricular and extracurricular activities. The P5 program has a significant impact on student character formation. They become more confident, responsible, and able to work together in a team. The implementation of P5 which is integrated with creative economy learning and recycling design gives students the freedom to develop their own potential according to their interests